2020
DOI: 10.3390/su12052018
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Sites in Small Towns—A Sustainability Assessment of Northumberland County

Abstract: Background: Land-use change, resulting from urban expansion, has led to the unprecedented importance of rethinking our interactions with the environment in general. The consequences of anthropogenic activity on natural land, as well as sustainable land use types, is a significant concern to the detriment of small towns. In this article, I assess the changes in the urban footprint morphology of Northumberland County while evaluating the consequences of urban fragmentation on archaeological sites. Northumberland… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Urbanization does not only deal with land-use change but also with lifestyle changes that concern rural-urban relationships in agriculture [16]. Similarly, the expansion of urban areas and continued sprawl is negatively affecting our environment and natural rural landscapes [17][18][19]. Subsequently, this can lead to contamination of soil, water, and air [20] and greenhouse gas emissions in urban-rural environments [21].…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization does not only deal with land-use change but also with lifestyle changes that concern rural-urban relationships in agriculture [16]. Similarly, the expansion of urban areas and continued sprawl is negatively affecting our environment and natural rural landscapes [17][18][19]. Subsequently, this can lead to contamination of soil, water, and air [20] and greenhouse gas emissions in urban-rural environments [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural heritage monuments and landscapes are threatened by various anthropogenic and natural hazards [ 1 , 2 , 3 ], including urbanization. Despite the urbanisation process being considered a relatively slow process compared to earthquakes and other hazard events that can have an immediate impact on cultural heritage sites, several studies indicated that urban sprawl can similarly impact the archaeological record of an area in the long term [ 4 , 5 ]. In addition, as [ 6 ] argue, new global challenges are expected in terms of balancing cultural heritage conservation and addressing the requirements of the urbanization process.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing a degree of spatial association is particularly critical in archaeological research, as it might reveal complex social, cultural or depositional processes underlying spatial data patterning. Autocorrelation analysis has been commonplace in archaeological research since the early days of GIS (Kvamme, 1990), and different significance tests are now routinely applied in various archaeological projects at intra-site and inter-site (or landscape) scale (Carrer, 2017;Vaz, 2020).…”
Section: Introductionmentioning
confidence: 99%